NEW METHODS SUPPORT AND ACTIVITIES COMMUNICATION AND INFORMATICS AGENCY MEDAN CITY BASED ON KNOWLEDGE MANAGEMENT - Zaini, Faizal; Wirawan, Yani Yudha; Biringkanae, Pipa; Arta, Deddy Novie Citra (Jurnal Manajemen dan Bisnis, 2021)
Knowledge is an important asset to an organization. Knowledge management is a process carried out by an organization to obtain, identity, creating, sharing, and utilizing knowledge or knowledge within the organization. One of the knowledge development models Management that will be used is the Fahmi model an approach developed for implementing knowledge management on government. to support the process government and human resource management to achieve the goals of deep bureaucratic reform develop government human resources professional one. This paper described the readiness of the Local Government of Medan District in implementing e-government to support the North Sumatra Smart province initiative. The research method was carried out quantitatively and qualitatively. Quantitative data was carried out by surveying 30 employees in the Mandailing Natal Government, while qualitative data was carried out by open interviews with informants who came from the Office for Communication and Informatics Services. The study also presents several obstacles to the implementation of government and propose several recommendations as a step towards improvement.